Determination Of Acute Poisoning Properties Of Vitis L. Plant Condensed Water-Syrup (Molasses) (Eurasian Scientific Herald, 2024)
This article presents information on medicinal properties, chemical activity, and results of pharmacological examination of water-syrup with condensed grape juice.